Lovage—Levisticum officinale Koch. - James M. Stephens (EDIS)
This document provides an overview of lovage (Levisticum officinale), a perennial herb of Mediterranean origin valued for its culinary and medicinal uses. It describes the plant’s characteristics, cultivation methods suitable for Florida gardens, and its various applications, including use in confectionery, as a celery-like flavoring, and in traditional medicine. The document also notes related species such as Scottish and Canadian lovage, which are consumed as vegetables in different regions. Original publication date May 1994.